Program Mendengar Aktif untuk Ayah dengan Anak Usia 4 Hingga 6 Tahun - Oki Gunawan; Puji Lestari Suharso; Dini Pepen Daengsari (Universitas Islam Indonesia, 2018)
Today, fathers are more involved in children’s caretaking. This role has shifted the views about family. Fathers who had the function as breadwinners are now also taking the role as caregivers. Unfortunately there are still some inadequacy in caregiving by fathers, especially in communicating with children. This issue needs to be handled because father’s competence in caregiving affects the development of the children to produce positive behavior. Fathers need an intervention to increase their knowledge and skills to communicates with children. One intervention that gives maximum effect is by trained fathers to increase knowledge and skills on active listening. This research is a one group pretest and posttest design type which involved 5 young adult fathers with children aged 4-6 years old and was performed in Depok, West Java. The final result shows a significant differences in fathers’ active listening knowledge and skills before and after receiving the father active listening program.